Validation of Patient Perception Instruments for Junior Doctor Performance: a Factor Analysis - Kusmiati, Mia; Bahari, Rafidah; Hamid, Noor Aini Abdul; Sanip, Suhaila; Emilia, Ova (Universitas Islam Bandung, 2019)
The patient is an essential stakeholder within the medical healthcare system and an important stakeholder of the medical education program. The patients should be able to assess the performance of junior doctors in general practitioner residency to ensure their competency. Some instruments of patient assessment are available, but they do not adapt to local needs and context. This study aims to validate newly developed evaluation instruments from the patient’s perspective against the performance of a junior doctor in a teaching hospital. Fifty patients from outpatient clinics of internal medicine of two teaching hospital Faculty of Medicine Universitas Islam Bandung were selected to fill out the questionnaire in September–October 2018. The tool consists of 20 items and used a 4-point Likert scale of strongly disagree, disagree, agree, and strongly agree. The SPSS version 21 have used to extract the data as the principal axis factoring of analysis. Oblimin rotation method was applied with Kaiser normalization to simplify and describe the data structure. The detailed analysis identified five factors based on the initial eigenvalue >1. Patient perception instruments of junior doctor performance (PIJDP) showed that five constructs extracted explained 81.27% of the variance of them. Constructs were namely: humanism, responsibility-accountability, communication-empathy, altruism, and pleasant manner. Construct validity achieved after the PIJDP run fifteen times, and consistency internal with Cronbach’s alpha was 0.95. In conclusions, the PIJDP could be used to assess the performance of junior doctors and could make a novel contribution to the development of medical education. VALIDASI INSTRUMEN PERSEPSI PASIEN TERHADAP KINERJA DOKTER MUDA: SEBUAH ANALISIS FAKTORPasien merupakan stakeholder kunci dalam sistem pelayanan kesehatan dan stakeholder penting dalam program pendidikan kedokteran. Pasien dapat menilai kinerja dokter muda dalam pemagangan umum untuk memastikan kompetensi mereka. Beberapa instrumen penilaian pasien sudah dibuat, namun mereka tidak diadaptasi terhadap kebutuhan dan konteks lokal. Penelitian ini bertujuan memvalidasi instrumen evaluasi yang baru dikembangkan menurut perspektif pasien terhadap kinerja dokter muda di rumah sakit pendidikan. Lima puluh pasien dari klinik rawat jalan penyakit dalam dua rumah sakit pendidikan Fakultas Kedokteran Universitas Islam Bandung dipilih untuk mengisi kuesioner pada September–Oktober 2018. Kuesioner berisi 20 item yang menggunakan Skala Likert empat poin dari sangat tidak setuju, tidak setuju, setuju, dan sangat setuju. SPSS versi 21 digunakan untuk menganalisis data melalui principal axis factoring. Metode rotasi oblimin dengan normalisasi Kaiser diaplikasikan untuk menyederhanakan dan menjelaskan struktur data. Hasil analisis mengidentifikasi lima faktor berdasar atas eigenvalue awal >1. Instrument persepsi pasien terhadap kinerja dokter muda (PIJDP) menggambarkan 5 construct yang diekstraksi sebesar 81,27% dari varian indikator dapat dijelaskan oleh faktor yang terbentuk. Faktor tersebut adalah humanisme, tanggung jawab-akuntabilitas, komunikasi-empati, altruisme, dan sifat menyenangkan. Kesahihan construct dicapai setelah PIJDP diulang lima belas kali dan konsistensi internal dengan Cronbach’s alpha sebesar 0,95. Simpulan, PIJDP dapat digunakan untuk menilai kinerja dokter muda dan dapat memberi kontribusi baru dalam pengembangan pendidikan kedokteran.